Peso ao nascer e sua associação com pressão arterial e estado nutricional na adolescência - Ferreira, Vanessa Roriz (2013)
Individuals with extreme birth weights, consequence of inadequate intrauterine development, are prone to developing diseases in adult life, phenomenon called “programming” or “fetal origin of diseases hypothesis”. The objective of this study was to investigate the association between birth weight, blood pressure and nutritional status of adolescents. It is a cross-sectional study performed in Goiânia/GO in 2010-2011. The study analyzed 829 adolescents, aged between 12 and 18, enrolled in public and private schools of the capital city. It was investigated birth weight, blood pressure, through four office measurements and through home blood pressure and nutritional status, through body mass index by age, height index for the age and waist circumference. Low (< 2.5 kg) and high birth weight (≥ 4 kg) prevalence in this population was 8.7% and 9.0%, respectively. Overweight presented high prevalence in both genders (22.9%), more sharply in boys (29.2%), compared to girls (18.1%) (p<0.01). Low weight reached less than 4% of adolescents, with similar expression between genders. Mild low height occurred in approximately 6% of adolescents, with considerable predominance in females (7.9%) in regard to males (3.9%) (p<0.018). Higher office blood pressure frequency in boys (11.0%) when compared to girls (6.6%) (p=0,029) was observed. Alterations in home blood pressure (3.8%) were significantly below those observed for office blood pressure (8.5%). Low height odds ratio was 2.4 times higher among adolescents with low birth weight (IC 95%= 1.1-5.1; p=0.027). In the simple linear regression analysis, for each 100 g increase in birth weight, height increased by 0.33 cm (IC 95%= 0.23-0.43; p<0.01). After multiple analysis, the increase was of 0.28 cm (IC 95%=0.18-0.37; p<0.01). Birth weight did not influence the blood pressure (office and home) of adolescents (p>0.05). Initially, birth weight elevation increased the body mass index and the waist circumference of adolescents, however, this relation was not sustained statistically significant after adjustment for confounding variables. It is concluded that birth weight is associated to height in adolescence, reinforcing the plausibility of fetal programming. In this perspective, maternal health promotion, focusing on adequate nutrition and prenatal, would increase the survival chance of the newborn and avoid growth problems in childhood and adolescence.